SIMULATION OF THE EFFECT OF THE COVER GLASS ANGLE INCLINE ON A SINGLE SLOPE SOLAR DISTILLATOR - Caturwati, Ni Ketut; Wahyudi, Hadi; Alda, Apriyani; Wiyono, Slamet; Dwinanto, Dwinanto (Department of Mechanical Engineering, Universitas Sultan Ageng Tirtayasa, 2024)
Distillation is a water purification process through evaporation and condensation. Research on solar distillation was developed using the Computational Fluid Dynamic (CFD) method to obtain an overview of the transmission of solar radiation heat by the cover glass for variations in the angle of the glass inclination of 100, 200 and 300. The water height in the basin is 100 mm. The simulation results show that the heating process with variations in the angle of the cover glass affects the distillation results. The smaller angle of the cover glass inclination, the higher heat flux entering the basin so that the evaporation process becomes higher which ultimately increases the amount of distillate water production produced. The highest heat flux entering the distillation system was achieved by the system with a cover glass inclination angle of 100 with a value of 388.525 W / m2, while the lowest was at an angle of 300 with a value of 379.792 W / m2. In addition, the highest distillate production was obtained on the cover glass with an inclination angle of 10 ° of 1.078 cc. For operational hours at 13.00 WIB and simulation time 180 seconds.